Telaah Fiqih Siyasah pada Pembatalan Peraturan Walikota Bengkulu oleh Gubernur Terkait Nilai Dasar Tanah dan Bangunan - Frediansyah; Imam Mahdi; Ismail Jalili (CV. Doki Course and Training, 2025)
This study aims to analyze the provisions of the legislation governing the cancellation of a legal product and examine it from the perspective of siyasah dusturiyah, in order to obtain a description of the harmonization and synchronization between government elements. This study uses a conceptual normative legal approach and a statute approach. The data collection method is carried out by tracing primary and secondary legal materials, which are then inventoried and classified according to the problems discussed. Data analysis is carried out by systematically reviewing and processing the legal materials that have been collected to answer the formulated legal issues. The results of the study indicate that from the perspective of fiqh siyasah, the Bengkulu Mayor Regulation Number 43 of 2019 concerning the Basis for Clarification of the Collection of Land and Building Acquisition Fees (BPHTB), which is enforced in the Bengkulu City community, needs to be reviewed. This is because its impact causes more harm than benefit to the community. Thus, a review of the regulation is important to ensure the principles of justice and benefit in regional governance.